2012
DOI: 10.1111/j.1460-9568.2012.08280.x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte activation and wound healing in intact‐skull mouse after focal brain injury

Abstract: Localized brain tissue damage activates surrounding astrocytes, which significantly influences subsequent long-term pathological processes. Most existing focal brain injury models in rodents employ craniotomy to localize mechanical insults. However, the craniotomy procedure itself induces gliosis. To investigate perilesional astrocyte activation under conditions where the skull is intact, we created focal brain injuries using light exposure through a cranial window made by thinning the skull that does not indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
6
30
0
Order By: Relevance
“…The data corroborate previous reports in SCN-lesioned Syrian hamsters (Guo et al, 2006) and mice (Guo et al, 2005) which demonstrated peripheral arrhythmia following loss of SCN-derived time information, suggesting that the SCN is a pacemaker, rather than a phase-coordinator, of peripheral oscillators (Guo et al, 2006). Importantly, the present data demonstrate peripheral immunological arrhythmia in neurologically-intact, unoperated hamsters, permitting the inference that neither the loss of fibers of passage, nor pathological inflammatory (Norenburg, 1994; Suzuki et al, 2012) or neuroendocrine (Bartness et al, 1991; Bittman et al, 1991) sequelae common to postoperative physiology are responsible for the loss of peripheral tissue oscillations. Rather, the mere dampening of rhythms in clock gene expression in the SCN is sufficient to disengage immunological peripheral oscillators from the central pacemaker.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The data corroborate previous reports in SCN-lesioned Syrian hamsters (Guo et al, 2006) and mice (Guo et al, 2005) which demonstrated peripheral arrhythmia following loss of SCN-derived time information, suggesting that the SCN is a pacemaker, rather than a phase-coordinator, of peripheral oscillators (Guo et al, 2006). Importantly, the present data demonstrate peripheral immunological arrhythmia in neurologically-intact, unoperated hamsters, permitting the inference that neither the loss of fibers of passage, nor pathological inflammatory (Norenburg, 1994; Suzuki et al, 2012) or neuroendocrine (Bartness et al, 1991; Bittman et al, 1991) sequelae common to postoperative physiology are responsible for the loss of peripheral tissue oscillations. Rather, the mere dampening of rhythms in clock gene expression in the SCN is sufficient to disengage immunological peripheral oscillators from the central pacemaker.…”
Section: Discussionsupporting
confidence: 56%
“…Critical to the interpretation of the present data is that DPS-induced arrhythmic hamsters, unlike SCN ablation models of arrhythmia, did not sustain trauma or injury to the CNS. Brain lesions result in CNS inflammation that persists for months after surgery (Norenburg, 1994; Suzuki et al, 2012), and bone remodeling and cutaneous wound healing that continues for the remainder of the lifespan (Lalani et al, 1998)— processes which permanently alter immune function and confound interpretation of measures of immunity. In contrast to lesion models, DPS-induced ARR hamsters differ from ENTR controls only in that the pacemaker in the SCN is driven to a state of near zero amplitude (Steinlechner et al, 2002); expression of core circadian clock genes in the SCN is low-amplitude and arrhythmic (Grone et al, 2011), giving rise to profound arrhythmia in locomotor activity, sleep, and body temperature (Larkin et al, 2004; Ruby et al, 2009) and eliminating nocturnal melatonin secretion (Steinlechner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct types of peri‐lesional reactive astrocyte have been identified by GFAP upregulation and hypertrophy. In lesion‐proximity regions the reactive astrocytes proliferated and expressed nestin, whereas in regions distal to the injury core the astrocytes exhibited increased GFAP, did not proliferate, lacked nestin expression and displayed different morphology …”
Section: Discussionmentioning
confidence: 99%
“…This results in a myriad of genotypic and phenotypic changes, which have complex effects on the architecture and function of surrounding brain parenchyma. In general, astrocytes within the lesion penumbra undergo cellular hypertrophy [16,24,26,37] with up-regulation of glial fibrillary acidic protein (GFAP) expression [33,37e44]. These changes are in part regulated by an array of growth factors, cytokines and chemokines.…”
Section: In Vivo Responses To Traumatic Brain Injurymentioning
confidence: 99%